Analisis Kinerja Bendung Berdasarkan Aspek dan Fungsi Struktur Bangunan: Studi Kasus: Bendung Batu Bassi Kabupaten Maros - Muyassar, Muhammad; Badrun, Burhanuddin; Yusuf, Andi Rumpang (Program Studi Teknik Sipil Universitas Bosowa, 2023)
This study aims to obtain: (1) the weight of the Batu Bassi Weir component which can be obtained as an indicator of the performance of the weir based on the condition and function of the building., (2) Analyzing the performance of the Batu Bassi Weir based on the condition and function of the building.This study took place at Batu Bassi Dam, located in Jene Taesa Village, Simbang District, Maros Regency, South Sulawesi Province. The data collection technique was carried out by direct observation in the field which then processed the data. From the results of data processing, the condition and function of the Bassi Weir were analyzed and interpreted. Data Analysis Using the ePAKSI Application Method (electronic Asset Management and Irrigation System Performance)..Results Analysis of the analyzed data by weighting using the Epaksi application to determine the relationship between the components of the dam performance. As for the results, the weighting is carried out using the Epaksi application to determine the relationship between the components of the performance of the weir. The results of the weighting of the dam performance components are as follows: 74% crest weight, 42% weir wing weight, 73% weir floor (dwelling pool), 70% embankment, 70% service bridge, 30% operating board, 70% ruler, safety fence 70%, 82% Drain Door, and 82% Intake Door. The condition of the Batu Bassi Weir Performance component is that the components in the Bassi Stone Weir are damaged by 25.08% and the condition of the weir is moderately damaged. The function of the component performance on the Bassi Stone Weir is 74.92% and requires extensive (quite large) maintenance.